(untitled) (Journal of Organizational Psychology, 2021)
The purpose of this study was to validate an inclusive, holistic, evidence-based index to measure the impact of organizational culture on employee wellbeing. This study utilized a new Cultural Wellbeing Index (CWI), a composite of other validated cultural metrics including inputs of hope, trust, and belonging. Internal validity of the index was measured using Cronbach’s alpha and Pearson correlation. Four logistic regression models were completed to test the correlative power of the CWI to employee health, retention, engagement, and job satisfaction. CWI shows strong internal validity and strong correlative and predictive power with employee wellbeing metrics among the population surveyed.